Assessing Fire‐Damage in Historical Papers and Alleviating Damage with Soft Cellulose Nanofibers. Issue 13 (4th February 2022) - Völkel, Laura; Beaumont, Marco; Johansson, Leena‐Sisko; Czibula, Caterina; Rusakov, Dmitrii; Mautner, Andreas; Teichert, Christian; Kontturi, Eero; Rosenau, Thomas; Potthast, Antje
Abstract: The conservation of historical paper objects with high cultural value is an important societal task. Papers that have been severely damaged by fire, heat, and extinguishing water, are a particularly challenging case, because of the complexity and severity of damage patterns. In‐depth analysis of fire‐damaged papers, by means of examples from the catastrophic fire in a 17th‐century German library, shows the changes, which proceeded from the margin to the center, to go beyond surface charring and formation of hydrophobic carbon‐rich layers. The charred paper exhibits structural changes in the nano‐ and micro‐range, with increased porosity and water sorption. In less charred areas, cellulose is affected by both chain cleavage and cross‐linking. Based on these results and conclusions with regard to adhesion of auxiliaries, a stabilization method is developed, which coats the damaged paper with a thin layer of cellulose nanofibers. It enables the reliable preservation of the paper and—most importantly—retrieval of the contained historical information: the nanofibers form a flexible, transparent film on the surface and adhere strongly to the damaged matrix, greatly reducing its fragility, giving it stability, and enabling digitization and further handling. Abstract : Fires have catastrophic effects of damage on books and papers and drastic optical and chemical‐physical changes occur. These changes are studied analytically in detail and are critically discussed. A stabilization method for heat‐damaged papers using cellulose nanofibers is established. The transparent nano‐coating adheres strongly to the damaged matrix, greatly reduces fragility, and enables digitization and further handling.